Low-temperature double-effect rare earth-based nanosheet catalyst as well as preparation method and application thereof
By using CEO2 and CUO as dual -effect activity components, V2O5 is a catalyst, and the low -temperature dual -effect rare earth base nano tablet catalysts of the modified powder coal ash nano -nano -nanoil are the problem of damaging the existing catalyst in the complex atmosphere. The effect of efficient NOX and SO2 at low temperatures.
Patent Information
- Application Number
- CN202411451841.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
Existing catalysts are prone to hydrolysis, corrosion or collapse in complex atmospheres containing water vapor and SO2, resulting in shortening of service life and high flue gas treatment costs.
Use CEO2 and CUO as dual-acting activity components, V2O5 as a catalyst, nanos tablets made of modified powder and coal ash are carriers, hydrochloric acid and acetyl propyol mixtures are as morphological control agents. Low -temperature dual -effect rare earth base nano tablet catalyst.
This catalyst not only has an efficient catalytic NOX at low temperature, but also catalyze the oxidation SO2 at the same time, avoiding the physical sulfur poisoning of the catalyst, and the preparation process is simple and the production input cost is low.
Smart Images

Figure CN119327472A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalytic material for environmental purification, in particular to a low-temperature double-effect rare earth-based nanosheet catalyst and a preparation method and application thereof, belonging to the technical field of environmental catalytic purification. Background Art
[0002] Nitrogen oxides (NO x ) is one of the causes of pollutants such as smog and acid rain. At present, the flue gas pollutants emitted by the steel sintering industry are complex in composition, and the flue gas denitrification catalyst is easily poisoned by sulfur, resulting in a shortened life. Selective catalytic reduction denitrification technology has high efficiency and good stability, and its technical core is the denitrification catalyst. The development of low-temperature dual-effect rare earth-based nanosheet catalysts can not only treat NO in the steel sintering industry, but also reduce the NO in the steel sintering industry. x , and can simultaneously treat SO2 and reduce catalyst sulfur poisoning, which is an important direction with practical significance and theoretical needs.
[0003] At present, a large number of research technologies at home and abroad have disclosed various types of denitrification catalysts and their preparation processes. For example, patent document CN202111049719.0 uses nano-titanium dioxide as a catalyst carrier, cobalt oxide, manganese oxide, and copper oxide as active substances, and adopts a step-by-step precipitation method to prepare an integrated catalyst for denitrification, de-dioxin, and de-VOCs. Patent document CN202211448628.9 uses a wet method to simultaneously / synergistically treat NO x , NH3 and VOCs, will contain NO x The flue gas or waste gas containing NH3 and VOCs is discharged after being absorbed and purified by the absorption tower, and the absorption liquid contains a composite oxidant. Patent documents CN201310153273.5 and patent document CN201310153875.0 both use manganese and cerium as active components, and the catalyst has high denitration activity and strong resistance to alkali metal poisoning; Patent document CN201310693174.6 uses metal oxides such as manganese, iron, copper and cerium as active components, adds tungsten and molybdenum polyacids as additives, and uses metal oxides such as titanium, aluminum and silicon as carriers. The prepared low-temperature denitration catalyst has a denitration rate of 90% in the temperature range of 125 to 200°C; Patent document CN115282752A discloses a pre-oxidation and tempering coupled catalytic low-temperature flue gas NO x In the collaborative removal method of VOCs, a pre-oxidant is used to partially oxidize NO to NO2. The pre-oxidant used is easy to decompose, making NO x The low-temperature flue gas with VOCs is first pre-oxidized, and the NO in the flue gas is partially oxidized to NO2 by pre-oxidation, and then synergistic catalysis is performed to reduce the NO in the flue gas under the action of ammonia, oxygen and a bifunctional catalyst. xThe catalyst is easily hydrolyzed, corroded or collapsed in a complex atmosphere containing water vapor and SO2, which is not conducive to the practical application of the catalyst. Summary of the invention
[0004] Aiming at the problem that the catalytic materials in the prior art are easily hydrolyzed, corroded or collapsed in a complex atmosphere containing water vapor and SO2, which is not conducive to the practical application of the catalyst, the present invention provides a low-temperature dual-effect rare earth-based nanosheet catalyst and a preparation method and application thereof. The catalyst of the present invention uses CeO2 and CuO as dual-effect active components, V2O5 as a co-catalyst, nanosheets made of modified fly ash as a carrier, and a mixture of hydrochloric acid and acetyl propanol as a morphology control agent. It is prepared by a hydrothermal-roasting method. The catalyst can not only catalyze the reduction of NO at low temperature with high efficiency, but also can effectively reduce the NO x , and can catalyze the oxidation of SO2 at the same time. The overall preparation process is simple, the production input cost is low, and it has excellent prospects for large-scale implementation and application.
[0005] In order to achieve the above technical objectives, the technical solutions adopted by the present invention are as follows:
[0006] According to a first embodiment of the present invention, a low-temperature dual-effect rare earth-based nanosheet catalyst is provided:
[0007] A low-temperature dual-effect rare earth-based nanosheet catalyst, characterized in that: the catalyst uses CeO2 and CuO as dual-effect active components, V2O5 as a co-catalyst, nanosheets made of modified fly ash as a carrier, a mixture of hydrochloric acid and acetyl propanol as a morphology control agent, and is prepared by a hydrothermal-roasting method.
[0008] Preferably, based on the mass of the nanosheet carrier made of modified fly ash, the mass percentage of the active component is 5% to 10%, the mass percentage of the co-catalyst is 3% to 5%, and the mass ratio of CeO2 and CuO in the active component is 1:0.5 to 1.
[0009] Preferably, the nanosheet carrier made of modified fly ash is obtained by first reacting fly ash with sodium silicate to obtain modified fly ash, and then using a mixture of hydrochloric acid and acetyl propanol as a morphology control agent to react to obtain nanosheets made of modified fly ash. The mixing mass ratio of hydrochloric acid to acetyl propanol is 1:0.3-0.8, preferably 1:0.4-0.7. The hydrochloric acid is a dilute hydrochloric acid solution with a mass fraction of 5-15%, preferably a dilute hydrochloric acid solution with a mass fraction of 10-15%.
[0010] According to a second embodiment of the present invention, a method for preparing a low-temperature dual-effect rare earth-based nanosheet catalyst is provided:
[0011] A method for preparing a low-temperature dual-effect rare earth-based nanosheet catalyst or a method for preparing a low-temperature dual-effect rare earth-based nanosheet catalyst as described in the first embodiment, the method comprising the following steps:
[0012] (1) Fly ash modification
[0013] The fly ash is ball-milled and then sieved to obtain fly ash powder, which is then added to dilute hydrochloric acid for acid washing, filtered and dried, and then added to ammonia water for alkali washing, and then filtered and dried again to obtain alkali-washed fly ash powder, and the alkali-washed fly ash powder, sodium silicate and deionized water are mixed, placed in a hydrothermal reactor for hydrothermal reaction, and then filtered and dried to obtain modified fly ash.
[0014] (2) Preparation of modified fly ash nanosheet carrier
[0015] The modified fly ash obtained in step (1), dilute hydrochloric acid, acetyl propanol and deionized water are mixed and placed in a hydrothermal reactor for secondary hydrothermal reaction. After filtering and drying, nanosheets are obtained and placed in ammonia water for alkaline washing. After filtering and drying again, they are placed in a muffle furnace for calcination to obtain modified fly ash nanosheet carriers.
[0016] (3) Preparation of dual-effect fly ash-based nanosheet catalyst
[0017] Weigh vanadium salt and citric acid monohydrate, dissolve in deionized water at 60-80° C. to obtain a catalyst precursor solution, then place the modified fly ash nanosheet carrier obtained in step (2) in the catalyst precursor solution, immerse, dry and calcine to obtain a modified fly ash nanosheet carrier loaded with a catalyst; weigh cerium salt, copper salt and citric acid monohydrate, dissolve in deionized water and stir evenly to obtain an active component precursor mixed solution, then place the modified fly ash nanosheet carrier loaded with a catalyst in the active component precursor mixed solution, immerse, dry and calcine to obtain a low-temperature dual-effect rare earth-based nanosheet catalyst.
[0018] Preferably, the ball milling apparatus in step (1) is a planetary horizontal ball mill, model PBGT-104W, the ball milling time is 30 to 60 minutes, the ball milling speed is 600 to 800 r / min, and the filtration mesh number used for sieving is 100 to 400 meshes.
[0019] Preferably, the dilute hydrochloric acid in step (1) is a hydrochloric acid solution with a mass fraction of 10 to 15%, the mass ratio of fly ash powder to dilute hydrochloric acid is 1:20 to 40, and the pickling time is 60 to 120 minutes.
[0020] Preferably, the ammonia water in step (1) is an ammonia water solution with a mass fraction of 10 to 20%, the mass ratio of fly ash powder to ammonia water is 1:10 to 30, and the alkali washing time is 60 to 120 minutes.
[0021] Preferably, in step (1), the mass ratio of fly ash powder after alkali washing, sodium silicate and deionized water is 1:0.5 to 1:40 to 60.
[0022] Preferably, the temperature of the hydrothermal reaction in step (1) is 120-160° C., the time of the hydrothermal reaction is 4-8 hours, the temperature of the drying is 80-100° C., and the time of the drying is 6-12 hours.
[0023] Preferably, in step (2), the mass ratio of the modified fly ash, dilute hydrochloric acid, acetyl propanol and deionized water is 1:0.2-0.4:0.1-0.3:40-60, and the dilute hydrochloric acid is a hydrochloric acid solution with a mass fraction of 10-15%.
[0024] Preferably, the temperature of the secondary hydrothermal reaction in step (2) is 140-160°C, the time of the secondary hydrothermal reaction is 12-24 hours, the ammonia water is 10-20% by mass, the mass ratio of the nanosheets to the ammonia water is 1:10-30, and the time of the alkali washing is 60-120 minutes.
[0025] Preferably, in step (2), the calcination temperature is 500-700° C., the calcination time is 2-4 h, the drying temperature is 80-100° C., and the drying time is 6-12 h.
[0026] Preferably, in step (3), the vanadium salt is ammonium metavanadate, and the mass ratio of the vanadium salt, citric acid monohydrate and deionized water is 1:1-2:40-60. The cerium salt is a hexahydrated cerium nitrate or a cerium chloride, the copper salt is a copper nitrate or a copper chloride, and the mass ratio of the cerium salt, citric acid monohydrate and deionized water is 1:2-4:4-10.
[0027] Preferably, the drying temperature in step (3) is 80-100°C, the drying time is 6-12 hours, the calcination temperature is 500-700°C, and the heating calcination time is 2-4 hours.
[0028] According to a third embodiment of the present invention, a low-temperature dual-effect rare earth-based nanosheet catalyst is provided:
[0029] A low-temperature dual-effect rare earth-based nanosheet catalyst or the use of the low-temperature dual-effect rare earth-based nanosheet catalyst as described in the first embodiment or the low-temperature dual-effect rare earth-based nanosheet catalyst prepared by the method described in the second embodiment, wherein the dual-effect rare earth-based nanocatalyst is used for treating flue gas in the steel industry (preferably the steel sintering industry) (mainly for catalytic reduction of nitrogen oxides in sintering flue gas and catalytic oxidation of dioxide streams).
[0030] Preferably, step (1) is as follows: the fly ash is ball-milled and then sieved to obtain fly ash powder (the ball milling instrument is a planetary horizontal ball mill, model PBGT-104W, the ball milling time is 30 to 60 minutes, the ball milling speed is 600 to 800 r / min; the filter mesh number used for sieving is 100 to 400 mesh). Then the fly ash (particle size distribution range is preferably between 100 and 400 mesh) is added to a dilute hydrochloric acid solution (mass fraction is 10 to 15%) for leaching (immersion for 60 to 120 minutes. The solid-liquid mass ratio during immersion is 1:20 to 40). After the immersion is completed, the fly ash is separated and dried (preferably at 80 to 100° C. for 6 to 12 hours). Then, the dried fly ash is added to an ammonia solution (mass fraction of 10-20%) for leaching (leaching for 60-120 minutes. The solid-liquid mass ratio during leaching is 1:10-30). After the leaching is completed, the fly ash is separated and dried (preferably dried at 80-100°C for 6-12 hours). Then, the dried fly ash is reacted with sodium silicate and deionized water in a reactor at 110-180°C (preferably 120-160°C) for 3-12 hours (preferably 4-8 hours). After the reaction is completed, the solid product is dried (preferably dried at 80-100°C for 6-12 hours) to obtain modified fly ash.
[0031] Preferably, step (2) is specifically as follows: reacting the modified fly ash, hydrochloric acid solution (mass fraction of 10-15%), acetyl propanol and deionized water in a reactor at 135-180° C. (preferably 140-160° C.) for 8-36 h (preferably 12-24 h); after the reaction, drying the solid product (preferably drying it at 60-100° C. for 3-15 h) and then alkali washing (preferably immersing it in an ammonia solution with a mass concentration of 10-25% for 60-120 min. The solid-liquid mass ratio during alkali washing is 1:10-30); after the alkali washing is completed, separating the solid product and drying it again (preferably drying it at 80-100° C. for 6-12 h); finally, placing the dried solid product in a muffle furnace and calcining it at 400-800° C. (preferably 500-700° C.) for 1-6 h (preferably 2-4 h) to obtain a nanosheet carrier.
[0032] Preferably, step (3) is specifically as follows: dissolving vanadium salt and monohydrated citric acid in deionized water (40-80°C) to obtain a catalyst precursor solution, then adding the nanosheet carrier obtained in step (2) to the catalyst precursor solution (preferably, the amount of the nanosheet carrier added is 0.2-0.8 times the mass of the catalyst precursor solution) for impregnation treatment for 40-150 min (preferably 60-120 min), and after the impregnation is completed, drying the solid product (preferably drying at 80-100°C for 6-12 h), and finally placing the dried solid product in a muffle furnace at 400-800°C (preferably 500-700°C) for calcination for 1-6 h (preferably 2-4 h) to obtain a nanosheet carrier loaded with a co-active component. Then, cerium salt, copper salt and monohydrated citric acid are dissolved in deionized water to obtain an active component precursor solution, and then the nanosheet carrier loaded with the auxiliary active component obtained above is added to the active component precursor solution (the amount of the nanosheet carrier loaded with the auxiliary active component is 0.5 to 2 times the mass of the active component precursor solution) for impregnation treatment for 40 to 150 minutes (preferably 60 to 120 minutes). After the impregnation is completed, the solid product is dried (preferably at 80 to 100° C. for 6 to 12 hours), and finally the dried solid product is placed in a muffle furnace and calcined at 400 to 800° C. (preferably 500 to 700° C.) for 1 to 6 hours (preferably 2 to 4 hours) to obtain a dual-effect rare earth-based nanocatalyst.
[0033] In the present invention, the flue gas emitted by the steel industry, such as sintering flue gas, contains not only a large amount of NO x , and it also contains a large amount of SO2 and water vapor. The existing low-temperature denitrification catalyst is prone to sulfur poisoning, hydrolysis, corrosion or collapse in this environment, which shortens the service life of the catalyst and requires frequent replacement of new catalysts, resulting in high flue gas treatment costs, which is not conducive to the practical application of the catalyst. x , SO2 and water vapor, etc., a dual-effect rare earth-based nanocatalyst was developed. The catalyst uses CeO2 and CuO with a specific composition as dual-effect active components, V2O5 as a co-catalyst, and specially prepared fly ash as a carrier. The catalyst is environmentally friendly and has excellent performance. It can not only convert NO x It can catalytically reduce SO2 into N2 and catalytically oxidize SO2 into SO3, thus achieving efficient purification of flue gas.
[0034] In the present invention, the carrier of the dual-effect rare earth-based nanocatalyst is made of ground fly ash powder (with a particle size range of 100 to 400 meshes) as a raw material, which is firstly acid-washed and alkaline-washed in sequence and then subjected to modification reaction with sodium silicate to obtain modified fly ash powder, and then the modified fly ash powder is used as a raw material, hydrochloric acid and acetyl n-propanol are used as morphology control agents, and then subjected to hydrothermal reaction and roasting treatment in sequence to obtain a modified fly ash nanosheet carrier. The carrier not only has a high specific surface area but also has a smooth microscopic sheet structure, which makes it difficult for SO3 formed by SO2 oxidation to adsorb on its microscopic surface, so that SO3 is more likely to react with water vapor in flue gas to form dilute sulfuric acid, thereby avoiding physical poisoning caused by the adsorption of ammonium bisulfate or ammonium bisulfite on the surface of conventional flue gas denitration catalysts, and can also promote the high value-added resource utilization of fly ash.
[0035] In the present invention, hydrochloric acid and acetyl n-propanol are used as morphology control agents to further modify the modified fly ash, mainly by hydrochloric acid and acetyl n-propanol and the partial metal (such as Al) contained in the fly ash to react, and then increase the hole of the fly ash, play a pore-making effect, help to improve the adsorption performance of the fly ash, and then make the carrier in the subsequent load catalytic active component (including main active component and auxiliary active component) can make the active component firmly attached to the carrier, ensure the catalytic performance of the catalyst itself while improving the cyclic stability of the catalyst. It should be noted that, when hydrochloric acid is used alone to carry out morphology treatment on the modified fly ash, due to the strong acidity of hydrochloric acid, it is easy to cause the fly ash pore-making transition and make the carrier pore too large, and then cause the active component to easily fall off. And when acetyl n-propanol is used alone to carry out morphology treatment on the modified fly ash, there is a weak pore-making effect, so that the carrier pore is insufficient, it is difficult to achieve the smooth implantation of the active component, and the catalytic performance of the catalyst is also affected. After in-depth research by the inventors, it was found that mixing hydrochloric acid and acetyl propanol to treat the morphology of modified fly ash can make the carrier pores at a better level, especially when the mass ratio of hydrochloric acid (preferably a dilute hydrochloric acid solution with a mass concentration of 8 to 20%) and acetyl propanol is between 1:0.3 and 0.8 (preferably 1:0.4 to 0.7), the pore-forming effect is best.
[0036] In the present invention, the dual-effect rare earth-based nanocatalyst of the present invention mainly uses CeO2 and CuO as dual-effect active components, and utilizes the excellent redox performance of CeO2 and the excellent oxidation performance of CuO to enable the catalyst to have excellent NO xIt has excellent reduction performance and SO2 oxidation performance. In addition, V2O5 is also used as an auxiliary active component. V2O5 is often used as a flue gas denitrification catalytic active component because of its excellent SCR performance, but because it also has good SO2 oxidation performance, in conventional SCR catalysts, oxidized SO3 will react with water vapor and ammonia in the flue gas to generate ammonium bisulfate, which is adsorbed on the catalyst surface, resulting in physical poisoning. The present invention adds V2O5 to the catalyst to promote the reduction performance of CeO2 and improve the oxidation performance of CuO. Moreover, because the nanosheet carrier avoids the adsorption of ammonium bisulfate or ammonium bisulfite, physical sulfur poisoning of the catalyst is also avoided.
[0037] The catalytic reaction conditions and results of the present invention are as follows: 0.5 g of a 40-60 mesh catalyst is taken and poured into a quartz tube with an inner diameter of 6 mm, the quartz tube is placed in a tubular furnace, and the heating reaction temperature is controlled by the tubular furnace. The laboratory gas is used to simulate flue gas, and the intake components are: NO (500 ppm), NH3 (500 ppm), O2 (11 vol.%), SO2 (200 ppm), water vapor (5 vol.%), and the rest are N2. The total gas flow rate is 500 mL / min. The Laoying 3021 portable carbon emission monitor is used to test the NO and SO2 concentrations. At 180°C, the NO removal efficiency is 100% after 5 minutes, and the SO2 oxidation rate is higher than 80%.
[0038] Compared with the prior art, the beneficial technical effects of the present invention are as follows:
[0039] The catalyst prepared by the present invention can not only efficiently catalyze the reduction of NO at low temperature, x , and can simultaneously catalyze the oxidation of SO2, so that SO2 in the flue gas can be brought into contact with water vapor to form dilute sulfuric acid in actual engineering applications. Compared with the prior art, this catalyst uses fly ash as raw material, and a mixture of hydrochloric acid and acetyl propanol as a morphology control agent to prepare a modified fly ash nanosheet carrier, which not only has a high specific surface area but also a smooth microscopic sheet structure, which makes it difficult for SO3 formed by the oxidation of SO2 to adsorb on its microscopic surface, making it easier for SO3 to react with water vapor in the flue gas to form dilute sulfuric acid, thereby avoiding the physical poisoning caused by the adsorption of ammonium bisulfate or ammonium bisulfite on the surface of conventional flue gas denitrification catalysts, and can also promote the high value-added resource utilization of fly ash. In addition, this catalyst uses CeO2 and CuO as dual-effect active components, and utilizes the excellent redox properties of CeO2 and the excellent oxidation properties of CuO to make the catalyst have excellent NO xReduction performance and SO2 oxidation performance. V2O5 is often used as a flue gas denitrification catalytic active component because of its excellent SCR performance, but because it also has good SO2 oxidation performance, in conventional SCR catalysts, the oxidized SO3 will react with water vapor and ammonia in the flue gas to generate ammonium bisulfate, which is adsorbed on the catalyst surface, resulting in physical poisoning. The addition of V2O5 to the catalyst of the present invention can not only promote the reduction performance of CeO2, but also improve the oxidation performance of CuO. Moreover, because the nanosheet carrier avoids the adsorption of ammonium bisulfate or ammonium bisulfite, the physical sulfur poisoning of the catalyst is also avoided.
[0040] 1: During the preparation process of the catalyst of the present invention, by adding a mixture of hydrochloric acid and acetyl propanol as a morphology control agent, the prepared catalyst can be made into a smooth microscopic flaky structure, thereby making it difficult for SO3 formed by oxidation of SO2 to adsorb on its microscopic surface, and more easily reacting with water vapor to form dilute sulfuric acid, thereby avoiding physical poisoning caused by the adsorption of ammonium bisulfate or ammonium bisulfite on the catalyst surface, and also promoting the high added value resource utilization of fly ash.
[0041] 2: The dual-effect rare earth-based nanocatalyst of the present invention can efficiently catalyze and reduce NO in flue gas from the steel sintering industry at low temperatures. x At the same time, it can also catalyze the oxidation of SO2. The catalyst has a high specific surface area, is environmentally friendly and has excellent catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a field emission scanning electron microscope image of the fly ash nanosheet carrier prepared in Example 1 of the present invention.
[0043] Figure 2 This is a field emission scanning electron microscope image of the fly ash nanosheet carrier prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0044] The present invention is further explained below in conjunction with specific implementation methods. It should be understood that these implementation methods are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.
[0045] Example 1
[0046] (1) Fly ash modification
[0047] Weigh 100g of fly ash and place it in a planetary horizontal ball mill, mill it at a speed of 600r / min for 60min, then sieve the fly ash after ball milling with 100-mesh and 200-mesh filter sieves to obtain fly ash powder of 100-200mesh, then weigh 10g of fly ash powder and add it to 200g of dilute hydrochloric acid with a mass fraction of 10%, soak and pickle for 120min; filter the mixture after pickling and place it in an oven at 80°C for 12h to obtain the mixture after pickling. The fly ash after acid washing is added into 100g of 10% ammonia water, and then soaked in alkali washing for 120min; the mixture after alkali washing is filtered and placed in an oven at 80°C for drying for 12h to obtain the fly ash after alkali washing; 5g of fly ash powder after alkali washing, 2.5g of sodium silicate and 200g of deionized water are weighed, mixed and stirred evenly, and then placed in a hydrothermal reactor at 120°C for hydrothermal reaction for 8h, filtered, and dried in an oven at 80°C for 12h to obtain the modified fly ash;
[0048] (2) Preparation of modified fly ash nanosheet carrier
[0049] 5 g of the modified fly ash obtained in step (1), 1 g of a 10% hydrochloric acid solution, 0.5 g of acetyl propanol and 200 g of deionized water were mixed and placed in a hydrothermal reactor for secondary hydrothermal reaction at 140° C. for 24 h, and then the mixture after the secondary hydrothermal reaction was filtered and placed in an oven at 80° C. for drying for 12 h to obtain nanosheets. The dried nanosheets were then placed in 50 g of a 10% ammonia solution for alkali washing for 120 min; after alkali washing, the nanosheets were filtered again and placed in an oven at 80° C. for drying for 12 h, and finally placed in a muffle furnace for calcination at 500° C. for 4 h to obtain a modified fly ash nanosheet carrier (the microscopic morphology of the carrier is shown in FIG. 1 ). Figure 1 );
[0050] (3) Preparation of dual-effect fly ash-based nanosheet catalyst
[0051] 0.116 g of ammonium metavanadate and 0.116 g of citric acid monohydrate are weighed and dissolved in 4.640 g of deionized water at a temperature of 60° C. to obtain a promoter precursor solution, then 3 g of the modified fly ash nanosheet carrier prepared in step (2) is placed in the promoter precursor solution, impregnated and placed in an oven at 80° C. to dry for 12 h, and then calcined at 500° C. for 4 h to obtain a modified fly ash nanosheet carrier loaded with a promoter; 0.252 g of cerium nitrate hexahydrate, 0.118 g of copper nitrate and 0.504 g of citric acid monohydrate are weighed and dissolved in 1.008 g of deionized water and stirred evenly to obtain an active component precursor mixed solution, then 3 g of the modified fly ash nanosheet carrier loaded with V2O5 is placed in the active component precursor mixed solution, impregnated and placed in an oven at 80° C. to dry for 12 h, and then calcined at 500° C. for 4 h to obtain a low-temperature dual-effect rare earth-based nanosheet catalyst.
[0052] (4) Catalyst activity test
[0053] Take 0.5g of 40-60 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, put the quartz tube in a tube furnace, and control the heating reaction temperature by the tube furnace. The laboratory gas is used to simulate the flue gas, and the intake components are: NO (500ppm), NH3 (500ppm), O2 (11vol.%), SO2 (200ppm), water vapor (5vol.%), and the rest are N2. The total gas flow rate is 500mL / min. The Laoying 3021 portable carbon emission monitor is used to test the NO and SO2 concentrations. At 180℃, the NO removal efficiency is 100% after 5min, and the SO2 oxidation rate is 85% (see Table 3 for specific data).
[0054] Example 2
[0055] (1) Fly ash modification
[0056] Weigh 100g of fly ash and place it in a planetary horizontal ball mill, ball mill it at a speed of 800r / min for 30min, then sieve the fly ash after ball milling with 300 mesh and 400 mesh filter screens to obtain 300-400 mesh fly ash powder, then weigh 10g of fly ash powder and add it to 400g of dilute hydrochloric acid with a mass fraction of 15%, soak and pickle for 60min; filter the mixture after pickling and place it in an oven at 100℃ for 6h to obtain pickling The fly ash after acid washing is added into 300g of 20% ammonia water by mass, and then soaked in alkali washing for 60min; the mixture after alkali washing is filtered and placed in an oven at 100°C for drying for 6h to obtain the fly ash after alkali washing; 5g of fly ash powder after alkali washing, 5g of sodium silicate and 300g of deionized water are weighed, mixed and stirred evenly, and then placed in a hydrothermal reactor at 160°C for hydrothermal reaction for 4h, filtered, and dried in an oven at 100°C for 6h to obtain the modified fly ash;
[0057] (2) Preparation of modified fly ash nanosheet carrier
[0058] 5 g of the modified fly ash obtained in step (1), 2 g of a 15% hydrochloric acid solution, 1.5 g of acetyl n-propanol and 300 g of deionized water are weighed and mixed, and the mixture is placed in a hydrothermal reactor for secondary hydrothermal reaction at 160° C. for 12 h, and then the mixture after the secondary hydrothermal reaction is filtered and placed in an oven at 100° C. for drying for 6 h to obtain nanosheets, and then the dried nanosheets are placed in 150 g of a 20% ammonia solution for alkali washing for 60 min; after alkali washing, the nanosheets are filtered again and placed in an oven at 100° C. for drying for 6 h, and finally placed in a muffle furnace for calcination at 700° C. for 2 h to obtain a modified fly ash nanosheet carrier;
[0059] (3) Preparation of dual-effect fly ash-based nanosheet catalyst
[0060] 0.193 g of ammonium metavanadate and 0.386 g of citric acid monohydrate were weighed and dissolved in 11.580 g of deionized water at a temperature of 80° C. to obtain a promoter precursor solution, then 3 g of the modified fly ash nanosheet carrier prepared in step (2) was placed in the promoter precursor solution, impregnated and placed in an oven at 100° C. for 6 hours, and then calcined at 700° C. for 2 hours to obtain a modified fly ash nanosheet carrier loaded with a promoter; 0.216 g of cerium chloride, 0.254 g of copper chloride and 0.920 g of citric acid monohydrate were weighed and dissolved in 2.300 g of deionized water and stirred evenly to obtain an active component precursor mixed solution, then 3 g of the modified fly ash nanosheet carrier loaded with V2O5 was placed in the active component precursor mixed solution, impregnated and placed in an oven at 100° C. for 6 hours, and then calcined at 700° C. for 2 hours to obtain a low-temperature dual-effect rare earth-based nanosheet catalyst.
[0061] (4) Catalyst activity test
[0062] Take 0.5g of 40-60 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, put the quartz tube in a tube furnace, and control the heating reaction temperature through the tube furnace. The laboratory gas is used to simulate the flue gas, and the intake components are: NO (500ppm), NH3 (500ppm), O2 (11vol.%), SO2 (200ppm), water vapor (5vol.%), and the rest are N2. The total gas flow rate is 500mL / min. The Laoying 3021 portable carbon emission monitor is used to test the NO and SO2 concentrations. At 180℃, the NO removal efficiency is 100% after 5min, and the SO2 oxidation rate is 89% (see Table 3 for specific data).
[0063] On the basis of Example 2, the effect of the change in the amount of morphology control agent on the catalyst was further studied to form Examples 3 to 6. The following table is a comparison table 1 of the changes in the amount of morphology control agent in Example 2 and Examples 3 to 6:
[0064] Table 1 shows the process control conditions of Examples 2-6
[0065]
[0066] Comparative Example 1
[0067] (1) Catalyst preparation
[0068] Except that the mixture of dilute hydrochloric acid and acetyl n-propanol as a morphology control agent is not added during the catalyst preparation, the other processes and conditions are the same as those in Example 1;
[0069] (2) Catalyst activity test
[0070] Take 0.5g of 40-60 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, put the quartz tube in a tube furnace, and control the heating reaction temperature through the tube furnace. The laboratory gas is used to simulate the flue gas, and the intake components are: NO (500ppm), NH3 (500ppm), O2 (11vol.%), SO2 (200ppm), water vapor (5vol.%), and the rest are N2. The total gas flow rate is 500mL / min. The Laoying 3021 portable carbon emission monitor is used to test the NO and SO2 concentrations. At 180℃, the NO removal efficiency is 76.5% after 5min, and the SO2 oxidation rate is 77.5% (see Table 3 for specific data);
[0071] (3) Contrast effect
[0072] Compared with Example 1, it can be seen that if the morphology control agent is not added during the preparation of the catalyst, the SO2 conversion rate of the catalyst decreases slightly and the NO conversion rate decreases significantly. This is mainly because after the morphology control agent is removed, the fly ash forms nanoparticles with smaller particle size ( Figure 2 ), but it does not have the ability to resist the adsorption of ammonium bisulfate, which causes the SO3 oxidized at low temperatures to easily form ammonium bisulfate and adsorb on the catalyst surface, resulting in physical poisoning of the catalyst, and ultimately leading to a significant decrease in the NO conversion rate. The adsorption of ammonium bisulfate will also reduce the contact between SO2 and the active sites of the catalyst, resulting in a slight decrease in the SO2 conversion rate.
[0073] Comparative Example 2
[0074] (1) Catalyst preparation
[0075] Except that copper salt is not added during the catalyst preparation, other processes and conditions are the same as those in Example 2;
[0076] (2) Catalyst activity test
[0077] Take 0.5g of 40-60 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, put the quartz tube in a tube furnace, and control the heating reaction temperature through the tube furnace. The laboratory gas is used to simulate the flue gas, the intake components are: NO (500ppm), NH3 (500ppm), O2 (11vol.%), SO2 (200ppm), water vapor (5vol.%), and the rest are N2. The total gas flow rate is 500mL / min. The Laoying 3021 portable carbon emission monitor is used to test the NO and SO2 concentrations. At 180℃, the NO removal efficiency is 88.6% after 5min, and the SO2 oxidation rate is 57.0% (see Table 3 for specific data);
[0078] (3) Contrast effect
[0079] Compared with Example 2, it can be seen that if CuO is not added during the preparation of the catalyst, although the catalyst has a higher V2O5 content, which makes up for part of the oxidation performance, the lack of CuO still causes the catalyst oxidation performance to drop sharply, thereby significantly reducing the SO2 oxidation performance of the catalyst; in addition, the CuO active site also has a certain ability to oxidize NO, converting NO into NO2, thereby promoting the rapid progress of the SCR reaction, so not adding CuO will also lead to a slight decrease in SCR performance.
[0080] On the basis of Example 1, the effect of a single morphology control agent on the catalyst was further studied to form Comparative Examples 3-4. The following table is a comparison table 2 of the changes in the amount of morphology control agent used in Example 1 and Comparative Examples 3-4:
[0081] Table 2 shows the process control conditions of Example 1 and Comparative Examples 3-4
[0082]
[0083] Catalytic activity test:
[0084] The catalysts prepared in Examples 3 to 6 and Comparative Examples 3 to 4 were subjected to the same catalyst activity test as in Examples 1 to 2 and Comparative Examples 1 to 2; the denitration test results of the catalysts prepared in each Example and Comparative Example are shown in Table 3 below:
[0085] Table 3 shows the NO conversion rate of the catalyst
[0086]
[0087] The catalysts prepared in Examples 3 to 6 and Comparative Examples 3 to 4 were subjected to the same catalyst activity test as in Examples 1 to 2 and Comparative Examples 1 to 2; the desulfurization test results of the catalysts prepared in each Example and Comparative Example are shown in Table 4 below:
[0088] Table 4 shows the SO2 conversion rate of the catalyst
[0089]
[0090] From the comparison of the catalytic performance test results in the above table, it can be seen that the catalyst containing specific components prepared by the special method of the present invention has excellent performance and can not only convert NO x It can catalytically reduce SO2 to N2 and catalytically oxidize SO2 to SO3, and can promote the high value-added resource utilization of fly ash; in addition, the catalyst is also environmentally friendly.
Claims
1. A low-temperature dual-effect rare earth-based nanosheet catalyst, characterized in that: The catalyst uses CeO2 and CuO as dual-effect active components, V2O5 as a co-catalyst, nanosheets made of modified fly ash as a carrier, and a mixture of hydrochloric acid and acetyl propanol as a morphology control agent. It is prepared by a hydrothermal-roasting method.
2. The catalyst according to claim 1, characterized in that: Based on the mass of the nanosheet carrier made of modified fly ash, the mass percentage of the active component is 5% to 10%, the mass percentage of the co-catalyst is 3% to 5%, and the mass ratio of CeO2 to CuO in the active component is 1:0.5-1.
3. The catalyst according to claim 1 or 2, characterized in that: The nanosheet carrier made of modified fly ash is prepared by first reacting fly ash with sodium silicate to obtain modified fly ash, and then using a mixture of hydrochloric acid and acetyl propanol as a morphology control agent to react to obtain nanosheets made of modified fly ash.
4. A method for preparing a low-temperature dual-effect rare earth-based nanosheet catalyst as claimed in any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) Fly ash modification The fly ash is ball-milled and then sieved to obtain fly ash powder, which is then added to dilute hydrochloric acid for acid washing, filtered and dried, and then added to ammonia water for alkali washing, which is filtered and dried again to obtain alkali-washed fly ash powder, and the alkali-washed fly ash powder, sodium silicate, and deionized water are mixed, placed in a hydrothermal reactor for hydrothermal reaction, and then filtered and dried to obtain modified fly ash; (2) Preparation of modified fly ash nanosheet carrier The modified fly ash obtained in step (1), dilute hydrochloric acid, acetyl propanol and deionized water are mixed and placed in a hydrothermal reactor for secondary hydrothermal reaction, filtered and dried to obtain nanosheets, and then placed in ammonia water for alkaline washing, filtered and dried again, and then placed in a muffle furnace for calcination to obtain a modified fly ash nanosheet carrier; (3) Preparation of dual-effect fly ash-based nanosheet catalyst Weigh vanadium salt and citric acid monohydrate, dissolve in deionized water at 60-80° C. to obtain a catalyst precursor solution, then place the modified fly ash nanosheet carrier obtained in step (2) in the catalyst precursor solution, immerse, dry and calcine to obtain a modified fly ash nanosheet carrier loaded with a catalyst; weigh cerium salt, copper salt and citric acid monohydrate, dissolve in deionized water and stir evenly to obtain an active component precursor mixed solution, then place the modified fly ash nanosheet carrier loaded with a catalyst in the active component precursor mixed solution, immerse, dry and calcine to obtain a low-temperature dual-effect rare earth-based nanosheet catalyst.
5. The method according to claim 4, characterized in that: The ball milling apparatus in step (1) is a planetary horizontal ball mill, model PBGT-104W, the ball milling time is 30 to 60 minutes, the ball milling speed is 600 to 800 r / min; the filter mesh number used for sieving is 100 to 400 meshes; and / or In step (1), the dilute hydrochloric acid is a hydrochloric acid solution with a mass fraction of 10 to 15%, the mass ratio of fly ash powder to dilute hydrochloric acid is 1:20 to 40, and the pickling time is 60 to 120 minutes; and / or In step (1), the ammonia water is an ammonia water solution with a mass fraction of 10-20%, the mass ratio of fly ash powder to ammonia water is 1:10-30, and the alkali washing time is 60-120 minutes.
6. The method according to claim 4, characterized in that: In step (1), the mass ratio of fly ash powder, sodium silicate and deionized water after alkali washing is 1:0.5 to 1:40 to 60; and / or In step (1), the temperature of the hydrothermal reaction is 120-160° C., and the time of the hydrothermal reaction is 4-8 hours; the temperature of the drying is 80-100° C., and the time of the drying is 6-12 hours.
7. The method according to claim 4, characterized in that: In step (2), the mass ratio of the modified fly ash, dilute hydrochloric acid, acetyl propanol and deionized water is 1:0.2-0.4:0.1-0.3:40-60, and the dilute hydrochloric acid is a hydrochloric acid solution with a mass fraction of 10-15%; and / or The temperature of the secondary hydrothermal reaction in step (2) is 140-160° C., the time of the secondary hydrothermal reaction is 12-24 hours; the ammonia water is a 10-20% ammonia water solution by mass, the mass ratio of the nanosheets to the ammonia water is 1:10-30, and the time of the alkali washing is 60-120 minutes; and / or In step (2), the calcination temperature is 500-700° C., the calcination time is 2-4 hours, the drying temperature is 80-100° C., and the drying time is 6-12 hours.
8. The method according to claim 4, characterized in that: In step (3), the vanadium salt is ammonium metavanadate, and the mass ratio of the vanadium salt, citric acid monohydrate and deionized water is 1:1-2:40-60; the cerium salt is a kind of cerium nitrate hexahydrate or cerium chloride, the copper salt is a kind of copper nitrate or copper chloride, and the mass ratio of the cerium salt, citric acid monohydrate and deionized water is 1:2-4:4-10.
9. The method according to claim 4, characterized in that: In step (3), the drying temperature is 80-100° C. and the drying time is 6-12 h; the calcination temperature is 500-700° C. and the heating calcination time is 2-4 h.
10. Use of a low-temperature dual-effect rare earth-based nanosheet catalyst as claimed in any one of claims 1 to 3 or a low-temperature dual-effect rare earth-based nanosheet catalyst prepared by the method as claimed in any one of claims 4 to 9, characterized in that: The low-temperature dual-effect rare earth-based nanosheet catalyst is used for treating flue gas in the steel industry; preferably, the low-temperature dual-effect rare earth-based nanosheet catalyst is used for treating flue gas in the steel sintering industry.
Citation Information
Patent Citations
Preparation method of alkali-poisoning-resistant denitrifying catalyst applicable to cement kilns
CN103230813A
Preparation method for high-specific surface anti-alkalosis denitration catalyst applicable to cement kiln
CN103263913A
A kind of SCR catalyst and preparation method thereof for cement kiln low-temperature flue gas denitrification
CN103638942B
Method for preparing denitration, dioxin removal and VOCs (Volatile Organic Compounds) removal integrated catalyst by fractional precipitation method and prepared catalyst
CN113877638A
Method for synergistically removing NOx and VOCs (Volatile Organic Compounds) in low-temperature flue gas through pre-oxidation conditioning coupled catalysis
CN115282752A
Cited By
Preparation method of catalyst for liquid-phase hydrofining of crude octanol
CN120205170A